Nephrotic Syndrome Gene TBC1D8B Is Required for Endosomal Maturation and Nephrin Endocytosis in Drosophila. Issue 12 (December 2022) - Milosavljevic, Julian; Lempicki, Camille; Lang, Konrad; Heinkele, Helena; Kampf, Lina L.; Leroy, Claire; Chen, Mengmeng; Gerstner, Lea; Spitz, Dominik; Wang, Minxian; Knob, Andrea U.; Kayser, Séverine; et al.
Significance Statement: Variants in TBC1D8B cause isolated nephrotic syndrome. TBC1D8B protein interacts with the slit diaphragm protein nephrin, but the pathogenesis remains unclear. We used Drosophila to elucidate the functional role of the recently discovered disease-causing gene. A null allele of Tbc1d8b in Drosophila exhibits a nephrocyte-restricted phenotype similar to patient presentation. Tbc1d8b protein localizes to mature early and late endosomes and promotes endosomal maturation and degradation, and is further required for nephrin transport. Expression of the murine ortholog rescues loss-of-function of the Drosophila TBC1D8B, which indicates evolutionary conservation. Discovery of two novel variants in TBC1D8B in a cohort of 363 patients with FSGS and functional validation in Drosophila suggest that TBC1D8B variants significantly underlie hereditary FSGS. Visual Abstract: Abstract : Background: Variants in TBC1D8B cause nephrotic syndrome. TBC1D8B is a GTPase-activating protein for Rab11 (RAB11-GAP) that interacts with nephrin, but how it controls nephrin trafficking or other podocyte functions remains unclear. Methods: We generated a stable deletion in Tbc1d8b and used microhomology-mediated end-joining for genome editing. Ex vivo functional assays utilized slit diaphragms in podocyte-like Drosophila nephrocytes. Manipulation of endocytic regulators and transgenesis of murine Tbc1d8b provided a comprehensive functional analysis of Tbc1d8b. Results: A null allele of Drosophila TBC1D8B exhibited a nephrocyte-restricted phenotype of nephrin mislocalization, similar to patients with isolated nephrotic syndrome who have variants in the gene. The protein was required for rapid nephrin turnover in nephrocytes and for endocytosis of nephrin induced by excessive Rab5 activity. The protein expressed from the Tbc1d8b locus bearing the edited tag predominantly localized to mature early and late endosomes. Tbc1d8b was required for endocytic cargo processing and degradation. Silencing Hrs, a regulator of endosomal maturation, phenocopied loss of Tbc1d8b . Low-level expression of murine TBC1D8B rescued loss of the Drosophila gene, indicating evolutionary conservation. Excessive murine TBC1D8B selectively disturbed nephrin dynamics. Finally, we discovered four novel TBC1D8B variants within a cohort of 363 patients with FSGS and validated a functional effect of two variants in Drosophila, suggesting a personalized platform for TBC1D8B -associated FSGS. Conclusions: Variants in TBC1D8B are not infrequent among patients with FSGS. TBC1D8B, functioning in endosomal maturation and degradation, is essential for nephrin trafficking.